2014
DOI: 10.4168/aair.2014.6.6.485
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Immediate Hypersensitivity Reactions to Cephalosporins

Abstract: Cephalosporins can cause a range of hypersensitivity reactions, including IgE-mediated, immediate reactions. Cephalosporin allergy has been reported with use of a specific cephalosporin, as a cross-reaction between different cephalosporins or as a cross-reaction to other β-lactam antibiotics. Unlike penicillins, the exact allergenic determinants of cephalosporins are less well understood and thus, standardized diagnostic skin testing is not available. Nevertheless, skin testing with diluted solutions of cephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 93 publications
(161 reference statements)
1
36
0
5
Order By: Relevance
“…12 The R1 side chain of cefazolin consists of a heterocycle N-methylthiodiazole structure 13 that is different to other cephalosporin R1 side chains. 8,12,27 In conclusion, our study demonstrates that diagnosis of cefazolin hypersensitivity benefits from a drug-specific intradermal test concentration of up to 20 mg/mL. Furthermore, the study of cross-reactivity reveals that, according to literature data, cefazolin hypersensitivity in the great majority of cases is a selective allergy with tolerance to other b-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…12 The R1 side chain of cefazolin consists of a heterocycle N-methylthiodiazole structure 13 that is different to other cephalosporin R1 side chains. 8,12,27 In conclusion, our study demonstrates that diagnosis of cefazolin hypersensitivity benefits from a drug-specific intradermal test concentration of up to 20 mg/mL. Furthermore, the study of cross-reactivity reveals that, according to literature data, cefazolin hypersensitivity in the great majority of cases is a selective allergy with tolerance to other b-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, clinical suspicion of cefazolin hypersensitivity is generally confirmed with skin tests. 8 However, for the time being, skin testing with cephalosporins is not entirely standardized and optimal skin test concentrations remain to be established. 8 Actually, sensitivity, specificity, and predictive values of this diagnostic method remain unknown, mainly because the maximal nonirritating skin test concentrations need to be established.…”
Section: Abbreviations Used Bp-benzylpenicillin Cd-cumulative Dose Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological agents may also differ from xenobiotics with regard to the clinical features of their adverse reactions . The disease for which the drug has been prescribed and concomitant treatments can both influence the adverse reactions to biological agents .…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no reliable cefazolin-specific IgE antibody assay, clinical suspicion of cefazolin hypersensitivity is generally confirmed by skin tests [12]. Although skin tests with cephalosporins are not as well established as with those with penicillin, several studies have demonstrated their usefulness for the diagnosis of immediate reactions [5, 6, 13].…”
Section: Introductionmentioning
confidence: 99%